Prostitution and sex work - Ditmore, Melissa Hope (Historical guides to controversial issues in America., 2011)
Prostitution and Sex Work is the first book since 1921 to offer a historic overview of this controversial topic and what our views on it say about American society. Exploring key people, places, and events, the guide includes descriptions of the myriad variations of the sale of sex and of the venues where prostitution occurs, as well as recurring themes such as panics about sexually transmitted diseases and the ever-present issue of violence in the sex trade. After reviewing the history of prostitution and sex work over the past 400 years, the book offers detailed information about the legal context of prostitution in America during the last century. It focuses particularly on the period since prostitution was criminalized during a panic over "white slavery" in the early 20th century, drawing parallels with current "sex trafficking" topics. An appendix of materials produced by sex workers is especially informative for those wishing to truly understand both sides of the issue.